Characterizing uplift load capacity of micropiles embedded in soil and rock considering inclined installation conditions. (April 2021) - Abbas, Qaisar; Choi, Wonseok; Kim, Garam; Kim, Incheol; Lee, Junhwan
Abstract: In this study, the uplift load-carrying behavior of inclined micropiles (MP) embedded in various soil-rock layer conditions was investigated. For this purpose, a series of model load tests and finite element analyses were performed. The focus was given on the effects of MP inclination angle (θ) and rock-embedded ratio (Zr /L). For MPs in rock, the uplift load capacity (Qu, θ ) was highest when vertically installed and decreased with increasing θ. The Qu, θ of MPs embedded in soil-rock mixed layers increased with Zr /L and decreased with increasing θ. Marked increases in Qu, θ were observed for Zr /L larger than 0.6 for all θs. As MPs inclination increased, the load-carrying mechanism shifted from the frictional resistance towards the passive resistance. The MPs inclined configuration caused less mobilization of the frictional resistance within the rock-embedded zone while producing the passive resistance within the upper soil zone. This explained the reductions in Qu, θ with increasing θ for MPs with the rock-embedded condition.